Effects of dispersed multiwalled carbon nanotubes on the micro-explosion and combustion characteristics of 2-methylfuran – diesel mixture droplets - Ittoo, Bhavishkar; Ooi, Jong Boon; Tran, Manh Vu; Jaliliantabar, Farzad; Najafi, Gholamhassan; Swamy, Varghese (Elsevier Ltd, 2022)
Isolated droplet combustion experiments have been carried out on neat diesel, a 15 vol% 2-methylfuran – 85 vol% diesel mixture (MF15), and nanofuels made from MF15 base fuel with addition of multiwalled carbon nanotubes (MWCNTs) at 25 ppm, 50 ppm, and 100 ppm concentrations (referred to as MF15C25, MF15C50, and MF15C100). Compared to MF15, the nanofuels displayed increased micro-explosion intensity and reduced micro-explosion occurrences, both effects being more pronounced at higher MWCNTs loadings. This behavior is attributed to the higher surface tension and viscosity of the nanofuels compared to that of MF15. The ignition delay decreased from 2.33 s to 1.71 s, the combustion rate constant increased from 0.82 mm2 s−1 to 1.01 mm2 s−1, and the combustion period reduced from 5.31 s to 4.54 s when going from pure MF15 to MF15C50. The improved combustion characteristics can be related to the superior thermal conductivity and large specific surface area of the dispersed MWCNTs in the nanofuels. The combustion characteristics of the nanofuel deteriorate at the highest MWCNTs dosing investigated here, possibly due to nanoparticle agglomeration. Overall, the present results suggest that dosing of MWCNTs at optimum levels improves the thermal efficiency and reduces the NOx emissions upon combustion of MF-diesel blends.